Pengelolaan Desa Wisata Rindu Hati Kabupaten Bengkulu Tengah Perspektif Maqashid Syari’ah - Herawati, Mesi; Afriyanty, Nonie (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2022)
This article aims to analyze the management of Rindu Hati Tourism Village from the perspective of Maqashid Syari’ah. The economic aspect of Islam is focused on the analysis of Maqashid Syari’ah, namely Hifdz Din (maintaining religion), Hifdz Aql (guarding reason), Hifdz Nasl (keeping offspring), Hifdz Nafs (guarding the soul), Hifdz Maal (keeping property). This study uses a qualitative descriptive method with the type of field research. The data used in this study are primary and secondary data analyzed by looking at the Maqashid Syari’ah aspect. The research results show that the management of Rindu Hati Tourism Village, from the perspective of Maqashid Syari’ah, has not met the five criteria of Maqashid Syari’ah as a whole. Still, only a few activities have been seen that lead to the maintenance of Maqashid Syari’ah.